Association of MTHFR missense variants with thromboembolic diseases and coagulation factor levels in European populations - Iyas Daghlas; Mengmeng Wang; Dipender Gill (Thrombosis Journal)
Abstract Background Investigations of the association between missense variants in the methylenetetrahydrofolate reductase (MTHFR) gene and thromboembolic diseases have been limited by small sample sizes. The effect of these variants on coagulation factor levels remains similarly uncertain. Objectives To test the association of the C677T and A1298C missense variants in MTHFR with risk of venous thromboembolism (VTE), cardioembolic stroke (CES), and circulating coagulation cascade protein levels. Patients/Methods We analyzed genetic associations of MTHFR missense variants with VTE (81,190 cases and 1,419,671 controls), CES (10,804 cases and 1,234,808 controls), and circulating levels of coagulation cascade proteins from the deCODE (n = 35,559) and UK Biobank (n = 46,218) cohorts. All participants in these genetic analyses were of European ancestry. We report odds ratios (OR) and beta coefficients per copy of the missense variant. VTE associations were compared to the effect of the Factor V Leiden variant. Results The A1298C variant conferred a small increased risk of VTE (OR per allele: 1.03, 95% confidence interval [CI] 1.02–1.04, P = 1.36 × 10− 6). This effect was 30-fold weaker than the effect of Factor V Leiden on VTE. After correction for multiple comparisons, the C677T variant did not demonstrate a significant association with VTE (OR 0.99, 95% CI 0.98-1.00, P = 0.04). Neither variant was associated with CES (P ≥ 0.18), nor with any of the 34 coagulation cascade proteins after correction for multiple comparisons. Conclusions These data do not support a role for MTHFR genetic testing as part of an inherited thrombophilia evaluation.